Implementasi Kepemimpinan Manajerial Untuk Meningkatkan Profesionalisme Guru Sd Negeri 11 Dan Sd Negeri 04 Kecamatan Tebat Karai Oleh Pengawas Sekolah Dasar Tahun Pelajaran 2015/2016 - Roza, Elia (UNIB Press, 2018)
Principal Managerial is the ability or ability shown by the principal to manage and utilize all components or areas of school work. This ability grows through the process of coaching and is supported by the factors that influence and lie behind it.The factors that affect a person's ability level is an element of maturity, related to the knowledge and skills that can be obtained from education, training, and experience.In the managerial implementation of the principal in this teacher, there is a positive influence on the creation of professionalism of teachers in teaching and learning activities, this is marked by a significant increase in each cycle, the first cycle of 69.2% and the second cycle of 91%. This demonstrates the successful leadership of the principal's managers towards teacher professionalism.